Major Traditional Probiotics: Comparative Genomic Analyses and Roles in Gut Microbiome of Eight Cohorts - Luo, Guangwen; Li, Bailiang; Yang, Cailu; Wang, Yutang; Bian, Xin; Li, Wan; Liu, Fei; Huo, Guicheng (Frontiers in Microbiology, 2019)
The opportunity of modulating gut microbiota to promote host health is increasingly recognized. Numerous people consume dietary products containing traditional probiotics in wish to improve their health, whereas short of research-based advices on how to select products with suitable probiotic species. Probiotic designers also sometimes felt confused how to design precision products for different consumers by taking advantages of different probiotic species’ strengths. However, there is lack of large-scale analyses on traditional probiotics complementarity potentials and their roles in gut microbiome related to common diseases. Here, we comprehensively analyzed 444 genomes of major traditional probiotics (sub) species (MTPS, n=15) by combining one newly sequenced genome with all of the public NCBI-available MTPS-related genomes, and used the public human fecal metagenomic data (n=1,815) from eight cohorts to examine the species enrichment direction in disease group or the control group to evaluate the roles of MTPS, compared to other main gut bacteria, in disease association. Our work provided a comprehensive genetic landscape and complementarity relations for MTPS, and shed light on personal probiotics supplement for consumers with different healthy state and urgent need that researchers and manufactures could explore novel probiotics other than traditional ones.